Eeg findings of posterior fossa tumors - Renda, Yavuz; Kalabay, Orhan; Yordam, Nurşen (The Turkish Journal of Pediatrics, 1972)
EEG obtained from 49 cases with posterior fossa tumors showed a high incidence of abnormality. Diffuse abnormalities were found in EEG’s of cases with midline tumors whereas in those with hemispherical tumors were mostly ipsilateral focal findings which inclined to project to the anterior head regions. EEG was found to be a helpful diagnostic method for posterior fossa tumors.